2020
DOI: 10.1016/j.crtox.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signal disruption, gonadal dysgenesis and reproductive disorders: Is there a link to endocrine disrupting chemicals?

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…In conclusion, we have shown that perinatal exposure to a chemical that has the capacity to antagonize the HH pathway may disrupt rodent ovary development. Although we saw no adverse effect in vivo in our study, it is likely that HH perturbation could affect theca cell recruitment as shown in vitro and similarly to effects postulated to take place in Leydig cells of the testes ( Johansson and Svingen, 2020 ). This would ultimately affect folliculogenesis, with negative impacts on fertility later in life, but also other female reproductive disorders such as polycystic ovarian syndrome, premature ovarian insufficiency and ovarian cancers, as these diseases are linked to compromised steroid hormone signaling originating from the ovarian steroidogenic cells, not least the theca lineage.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In conclusion, we have shown that perinatal exposure to a chemical that has the capacity to antagonize the HH pathway may disrupt rodent ovary development. Although we saw no adverse effect in vivo in our study, it is likely that HH perturbation could affect theca cell recruitment as shown in vitro and similarly to effects postulated to take place in Leydig cells of the testes ( Johansson and Svingen, 2020 ). This would ultimately affect folliculogenesis, with negative impacts on fertility later in life, but also other female reproductive disorders such as polycystic ovarian syndrome, premature ovarian insufficiency and ovarian cancers, as these diseases are linked to compromised steroid hormone signaling originating from the ovarian steroidogenic cells, not least the theca lineage.…”
Section: Discussionsupporting
confidence: 57%
“…As shown herein, gestational exposure to 50 mg/kg bw/day itraconazole induced no severe toxicity or teratogenicity, nor any effects on the ovaries; but a dose of 100 mg/kg bw/day induced teratogenicity in a previous study ( El-Shershaby et al , 2014 ), which is why we opted not to expose our rats to these high doses as it would render any potential effects on ovary development of secondary interest. Reproductive-specific effects at lower doses of HH inhibitors would therefore more likely only manifest in combination with inhibition of other hormone-sensitive signaling pathways, as recently discussed ( Johansson and Svingen, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hedgehog (HH) signaling is a highly conserved developmental pathway that relies on cholesterol interacting with specific sterol-binding proteins. Endocrine disruption is known to interfere with HH signaling ( Johansson and Svingen, 2020 ). Developmentally-regulated signaling pathways involving apoptosis, embryogenesis, cell proliferation, and development of diseases present in higher animals are also found in cnidarians including Exaiptasia ( Technau et al, 2005 ; Matus et al, 2008 ; Sinkovics, 2015 ; Bucher et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of endocrine-disrupting chemicals (EDCs) in the aetiology of ED is unclear. The WHO defines an EDC as "an exogenous substance or mixture that alters function(s) of the endocrine system and consequently causes adverse health effects in an intact organism, or its progeny, or (sub) populations" [Johansson and Svingen, 2020]. The term EDC in this review refers specifically to chemicals which are known to alter hormonal pathways and cause adverse health effects in humans.…”
mentioning
confidence: 99%